Studi Kuat Tekan Beton Speedcrete Dengan Zat Additive Naphthalene Berdasarkan Variasi Umur - Syifa Fauziah; Anisah Anisah; Sittati Musalamah (Menara: Jurnal Teknik Sipil, 2019)
This research aims to determine the maximum compressive strength value of concrete speedcrete using naphthalene additive additive at each test age and compare with normal concrete 28 days. This research used cylindrical test object with diameter 15 cm and height 30 cm. Speedcrete concrete does not undergo the treatment process while the normal concrete test object through the treatment process. Testing compressive strength of concrete speedcrete using Crushing Test Machine tool. In this research the compressive strength was produced by using superplasticizer type naphthalene and compared with normal concrete without using additive. The target quality plan is fc '35 MPa with the use of additive dose of 1.7% of the weight of cement. The results of this research showed an increase in the value of compressive strength of concrete speedcrete with aadditive materials added naphthalene increased with increasing age of concrete. The results showed that the compressive strength of concrete speedcrete with naphthalene additive materials of 12 hours, 18 hours, 28 hours and 48 hours was 0.5 MPa, 17,81 MPa, 31,14 MPa and 45,77 MPa. Normal strength concrete strength with the addition of 20% water age 28 days that is equal to 54.76 MPa.